2009
DOI: 10.2165/00007256-200939010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Natural Turf Surfaces

Abstract: It is well documented that health and social benefits can be attained through participation in sport and exercise. Participation, particularly in sports, benefits from appropriate surface provisions that are safe, affordable and high quality preferably across the recreational to elite continuum. Investment, construction and research into artificial sports surfaces have increased to meet this provision. However, not all sports (e.g. golf, rugby and cricket) are suited to training and match-play on artificial tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…Specifically, we found that the relationship between longitudinal and lateral movements was more balanced in the following configurations: age-group U8 <> 5v5 game format; U10 <> 7v7; U12 <> 9v9; and U14 <> 11v11, respectively. The more rounded shapes in the mentioned configurations reflect the similarity of movement amplitudes in the longitudinal and lateral direction, suggesting that the profile of the game in the respective configurations was more structured and collective from a tactical point of view (Bartlett, Button, Robins, Dutt-Mazumder, & Kennedy, 2012;Silva, Travassos, et al, 2014;Stiles, James, Dixon, & Guisasola, 2009). The relationship between longitudinal and lateral movements was not as balanced in the other configurations whose ellipse forms reflected a less balanced player-space relationship as well as a poorer player-function relationship according to specific areas of the pitch (Duarte, Araújo, Correia, & Davids, 2012).…”
Section: Relative Positioningmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, we found that the relationship between longitudinal and lateral movements was more balanced in the following configurations: age-group U8 <> 5v5 game format; U10 <> 7v7; U12 <> 9v9; and U14 <> 11v11, respectively. The more rounded shapes in the mentioned configurations reflect the similarity of movement amplitudes in the longitudinal and lateral direction, suggesting that the profile of the game in the respective configurations was more structured and collective from a tactical point of view (Bartlett, Button, Robins, Dutt-Mazumder, & Kennedy, 2012;Silva, Travassos, et al, 2014;Stiles, James, Dixon, & Guisasola, 2009). The relationship between longitudinal and lateral movements was not as balanced in the other configurations whose ellipse forms reflected a less balanced player-space relationship as well as a poorer player-function relationship according to specific areas of the pitch (Duarte, Araújo, Correia, & Davids, 2012).…”
Section: Relative Positioningmentioning
confidence: 90%
“…These absolute positions were also used to define the Cartesian reference coordinate systems for each game format, with its origin placed at the pitch centre. GPS Longitudinal and latitudinal (spherical) coordinates were converted into Cartesian coordinates with the Haversine formula (Sinnott, 1984). Fluctuations in players positions were reduced using a moving average filter with a time scale of (.2 s) and data resampling was employed to synchronise the time series of all players within each match condition (Silva et al, 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…Currently, two types of surfaces are sanctioned by FIFA and UEFA for soccer competition at the elite professional level: natural grass (NG) surfaces, and artificial turf surfaces (including both 3rd generation and 4th generation) otherwise referred to as “Football turf” (FT) [2]. The main reasons for the introduction of artificial turf were to lessen the impact of environmental conditions on surfaces, to decrease the high operating costs associated with NG, and to increase field usability [3-5]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in sports surface engineering have focussed on the relationship with injury and synthetic turf surfaces [1][2][3][4] as the number of 'third generation' longer-pile synthetic surfaces increases, in soccer in particular. For soccer and the majority of other 'winter field sports', the most common surface for play remains natural turf, however, and mechanical studies (beyond field measurement of traction and hardness) of natural turf are relatively rare, particularly in integration with sports injury or biomechanics studies [5].…”
Section: Introductionmentioning
confidence: 99%